Biomethane production through anaerobic co-digestion with Maize Cob Waste based on a biorefinery concept: A review. (1st November 2019) - Surra, Elena; Bernardo, Maria; Lapa, Nuno; Esteves, Isabel A.A.C.; Fonseca, Isabel; Mota, José P.B.
Abstract: Maize Cob Waste (MCW) is available worldwide in high amounts, as maize is the most produced cereal in the world. MCW is generally left in the crop fields, but due to its low biodegradability it has a negligible impact in soil fertility. Moreover, MCW can be used as substrate to balance the C/N ratio during the Anaerobic co-Digestion (AcoD) with other biodegradable substrates, and is an excellent precursor for the production of Activated Carbons (ACs). In this context, a biorefinery is theoretically discussed in the present review, based on the idea that MCW, after proper pre-treatment is valorised as precursor of ACs and as co-substrate in AcoD for biomethane generation. This paper provides an overview on different scientific and technological aspects that can be involved in the development of the proposed biorefinery; the major topics considered in this work are the following ones: (i) the most suitable pre-treatments of MCW prior to AcoD; (ii) AcoD process with regard to the critical parameters resulting from MCW pre-treatments; (iii) production of ACs using MCW as precursor, with the aim to use these ACs in biogas conditioning (H2 S removal) and upgrading (biomethane production), and (iv) an overview on biogas upgrading technologies. Graphical abstract: Image 1 Highlights: Maize Cob Waste (MCW) is available worldwide and is underutilised. Pre-treated MCW can be submitted to AcoD to improve C/N ratios. MCW is an excellent feedstock to produce Activated Carbons (ACs). ACs from MCW can be used for H2 S removal and biogas upgrading. Valorisation of MCW in a biorefinery contributes to agriculture sustainability.